2019
DOI: 10.1177/0022243719865516
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increasing Search Frictions on Online Shopping Behavior: Evidence from a Field Experiment

Abstract: Many online stores are designed such that shoppers can easily access any available discounted products. The authors propose that deliberately increasing search frictions by placing obstacles to locating discounted items can improve online retailers’ margins and even increase conversion. The authors demonstrate this using a simple theoretical framework that suggests inducing consumers to inspect higher-priced items first may simultaneously increase the average price of items sold and the overall expected purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…(2) Consumers' perceived benefits, channel trust, and switching cost have a positive impact on purchase intention, and the main factor for attracting consumers to choose online product purchasing is the perceived benefit factor, the greater the perceived benefits, the stronger the consumers' willingness to buy the products (e.g., Martin et al, 2015;van der Lans et al, 2016). (3) Consumers' willingness to search online also affects their willingness to buy online, and this result is consistent with the results found in the previous studies (e.g., Ngwe et al, 2019;Zhai et al, 2019); therefore, guiding consumers to search for products will increase purchasing probability of sold products. (4) When channel trust reaches a certain level, online channels have a certain channel lock, that is, consumers will choose the path of online search-online purchase, and channel switching cost also has a positive effect on the online channel lock, this is because the higher the perception of switching cost, the less likely it is for consumers to search for product information in one channel and purchase products in another channel (e.g., Anderson and Simester, 2013;Stan et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…(2) Consumers' perceived benefits, channel trust, and switching cost have a positive impact on purchase intention, and the main factor for attracting consumers to choose online product purchasing is the perceived benefit factor, the greater the perceived benefits, the stronger the consumers' willingness to buy the products (e.g., Martin et al, 2015;van der Lans et al, 2016). (3) Consumers' willingness to search online also affects their willingness to buy online, and this result is consistent with the results found in the previous studies (e.g., Ngwe et al, 2019;Zhai et al, 2019); therefore, guiding consumers to search for products will increase purchasing probability of sold products. (4) When channel trust reaches a certain level, online channels have a certain channel lock, that is, consumers will choose the path of online search-online purchase, and channel switching cost also has a positive effect on the online channel lock, this is because the higher the perception of switching cost, the less likely it is for consumers to search for product information in one channel and purchase products in another channel (e.g., Anderson and Simester, 2013;Stan et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…It is indicated by Singh and Swait (2017) that online channels provide greater searching or purchasing benefits. Ngwe et al (2019) found that guiding consumers to search for products will increase the overall expected purchasing probability of sold products. Zhai et al (2019) showed that the channel searching and purchasing behavior of consumers can influence each other.…”
Section: Hypotheses Search Intentionmentioning
confidence: 99%
“…Based on the effects of consistent exposure through advertisements offering discounts and promotions, consumers tend to make judgments on the advertised apparel (Fernández & González, 2020;Lee & Chen-Yu, 2018;Smith et al, 2019). This has successfully built a positive relationship between customers and selected products as found by previous studies (Anandya et al, 2017;Arifianti, 2013;Chang & Wildt, 1994;Dodds et al, 1991;Floh & Madlberger, 2013;Kim & Stoel, 2004;Ngwe et al, 2019;Xia et al, 2020).…”
Section: Promotionmentioning
confidence: 89%
“…consumers tend to avoid the risk of loss when the purchase reward is offered as a profit for themselves and this is used to influence the purchase intention (Tversky & Kahneman, 1991). Empirical studies show that promotion have a positive influence on impulsive purchasing decisions (Arifianti, 2013) general purchasing intentions (Chang & Wildt, 1994;Dodds, Monroe, & Grewal, 1991), online products (Anandya, Dudi, & Citra, 2017) and underwear sold online (Kim & Stoel, 2004;Ngwe, Ferreira, & Teixeira, 2019;Xia et al, 2020). Fernández and González (2020) found that kids are motivated by the low price and promotions in online shopping.…”
Section: Promotionmentioning
confidence: 99%
See 1 more Smart Citation